Pengaruh Ekspektasi Kinerja Pada Minat Pemanfaatan Internet Dan Efisiensi Biaya (Studi Pada Mahasiswa Magister Akuntansi) - Rina Kesuma Dewi, Anak Agung Sagung; Putra Astika, Ida Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This research is to get empirical evidence of the effect of the performance expectations of interest in Internet use in supporting students' learning activities, so as to improve the competence in the field of accounting and its impact on the efficiency of the costs incurred and interest felt by students through the use of the Internet. The population used is the Udayana University Master of Accounting students who are taking courses from the first semester to semester three. The sampling technique used convenience sampling. Samples numbered 83 people and analyzed using path analysis. The results showed that the positive effect on the performance expectations interest internet usage, internet usage interests positive effect on cost efficiency, performance expectations positive effect on cost efficiency, and performance expectations positive effect on cost efficiency through the use of internet interes. Keywords : performance expectation, internet utilizing interest, cost efficiency
Keywords: performance expectation, internet utilizing interest, cost efficiency